Economic development - Kindleberger, Charles P. (New York : McGraw-Hill, 1958)
This is a a text on economic development by Charles P. Kindleberger a Ford International Professor of Economics at the Massachusetts Institute of Technology. It covers topics like: the process of growth, land, capital, labour, technology and entrepreneurship, scale, transformation. Others include: population, regional cooperation amongs others foreign trade
lje 20/09/2018
Loans
Keywords: Economic development